PENGARUH KADAR LIMBAH KACA SEBAGAI SUBSTITUSI AGREGAT HALUS TERHADAP KARAKTERISTIK CAMPURAN ASPAL PORUS - Miftahul Fauziah; Fitri Sari Wijayati (Jurusan Teknik Sipil, Fakultas Teknik Sipil dan Perencanaan, Universitas Islam Indonesia, 2016)
Porous asphalt allows water to be more easily drained from the road surface into asphalt concrete pavement. It absorbs rainwater through the coarse aggregate, this may be a solution of flooding at most cities in Indonesia which is caused by continuous rain. Glass is one of waste that had not been much recycled and need to be considered, By using glass as a material substitution is expected to be longlife and has a strength equals or even better on asphalt mixtures. This research was conducted in order to find the effect of substitution levels of glass on Marshall characteristics, durability, value of indirect tensile strength, abrasion resistance and permeability according to specifications of Australia Asphalt Pavement Asociation (AAPA) 2004. The research was carried out by using variant levels of substituion glass on fine aggregate No.8 in mixture that are 0%, 10%, 20%, 30%, and 40%. The results show that the glass waste on fine aggregate No.8 can be used in porous asphalt mixture only to 30% of proportion. From the Marshall test the results showed that the mixture ability to withstand a load is increasing up to optimum limit and declined thereafter at stability value then the flow level, MQ, VITM, VMA which is increasing up to optimum limit also declined after that as for VFWA level and density is declining until certain level then rising thereafter. The ability toward impact with Cantabro test result is increased up to optimum limit. The mixture homogeneous is increased, it shows from value of Asphalt Flow Down that decreased continously with the increasing of glass waste proportion.